Vitreous and Vision Degrading Myodesopsia. (November 2020) - Sebag, J.
Abstract: Macromolecules comprise only 2% of vitreous, yet are responsible for its gel state, transparency, and physiologic function(s) within the eye. Myopia and aging alter collagen and hyaluronan association causing concurrent gel liquefaction and fibrous degeneration. The resulting vitreous opacities and collapse of the vitreous body during posterior vitreous detachment are the most common causes for the visual phenomenon of vitreous floaters . Previously considered innocuous, the vitreous opacities that cause floaters sometimes impact vision by profoundly degrading contrast sensitivity function and impairing quality-of-life. While many people adapt to vitreous floaters, clinically significant cases can be diagnosed with Vision Degrading Myodesopsia based upon echographic assessment of vitreous structure and by measuring contrast sensitivity function. Perhaps due to the ubiquity of floaters, the medical profession has to date largely ignored the plight of those with Vision Degrading Myodesopsia. Improved diagnostics will enable better disease staging and more accurate identification of severe cases that merit therapy. YAG laser treatments may occasionally be slightly effective, but vitrectomy is currently the definitive cure. Future developments will usher in more informative diagnostic approaches as well as safer and more effective therapeutic strategies. Improved laser treatments, new pharmacotherapies, and possibly non-invasive optical corrections are exciting new approaches to pursue. Ultimately, enhanced understanding of the underlying pathogenesis of Vision Degrading Myodesopsia should result in prevention, the ultimate goal of modern Medicine. Graphical abstract: Image 1 Highlights: Vitreous fills the center of the eye with a clear solid gel during youth. Myopia in youth and posterior vitreous detachment in aging cause vitreous floaters. Degradation in contrast sensitivity function impacts vision and quality of life. Vitrectomy normalizes vision and improves quality of life cost-effectively. Laser therapies or pharmacologic vitreolysis might replace surgery in the future.